If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H + 8 = 7 Reorder the terms: 8 + H = 7 Solving 8 + H = 7 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + H = 7 + -8 Combine like terms: 8 + -8 = 0 0 + H = 7 + -8 H = 7 + -8 Combine like terms: 7 + -8 = -1 H = -1 Simplifying H = -1
| 2/n=9/2 | | B+20=40 | | -19x^2+8x=0 | | 27p^3q^6-8q^6=0 | | 1/(b^(7/2)) | | f=-36x-1+9x | | -2(2c-4)= | | 1.8y=3.8 | | 9x^3/2-18=0 | | 0=x^2+3x+8 | | V/6.3=-7 | | 0=x+3x+8 | | f(x)=(x-4)(x+2) | | 2z^2-21z+3=39 | | (1/7)x=8 | | n=25+0.45n | | R=-30n^2+180n+3360 | | xsquared+15=24 | | (4x^2)-6x+3=0 | | 6(8+x)=48-11x | | 2c-12c= | | 6[2-(-3x-2)]=68x+99 | | 24+6-12x=60 | | -7.3t^2+8.25t+2.1=H | | 13(x-5)=12x-69 | | -88=8(1-4x) | | -7.3t^2+8.25t+2.1=x | | 1.63q=9.73 | | 8(a+7b-5)=8a+56b-72 | | 7=56y | | -7.3t^2+8.25+2.1=x | | 2x-7=2y-13 |